2018
DOI: 10.1038/s41598-018-26093-1
|View full text |Cite
|
Sign up to set email alerts
|

DNAJC17 is localized in nuclear speckles and interacts with splicing machinery components

Abstract: DNAJC17 is a heat shock protein (HSP40) family member, identified in mouse as susceptibility gene for congenital hypothyroidism. DNAJC17 knockout mouse embryos die prior to implantation. In humans, germline homozygous mutations in DNAJC17 have been found in syndromic retinal dystrophy patients, while heterozygous mutations represent candidate pathogenic events for myeloproliferative disorders. Despite widespread expression and involvement in human diseases, DNAJC17 function is still poorly understood. Herein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…These include the closely linked dual oxidase genes Duox1 and Duox2, and the dual oxidase maturation factor Duoxa2 that map within a 68 kb interval. Another candidate gene located 3.1 Mb proximal, Dnajc17, encodes a type III heat-shock protein-40 involved in splicing, which has been suggested as a candidate for Htrc2 (Pascarella et al 2018). This gene is hypothesized to be the modifier of thyroid gland development and function in Nkx2.1, Pax8 double heterozygotes and affects Tg transcription in cell culture (Amendola et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…These include the closely linked dual oxidase genes Duox1 and Duox2, and the dual oxidase maturation factor Duoxa2 that map within a 68 kb interval. Another candidate gene located 3.1 Mb proximal, Dnajc17, encodes a type III heat-shock protein-40 involved in splicing, which has been suggested as a candidate for Htrc2 (Pascarella et al 2018). This gene is hypothesized to be the modifier of thyroid gland development and function in Nkx2.1, Pax8 double heterozygotes and affects Tg transcription in cell culture (Amendola et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The proteins with largest regulations included DNAJC17 and possibly NDRG2. DNAJC17 is a heat shock protein family member known to be involved in splicing-related processes [ 33 ], but the function of DNAJC17 remains largely unknown [ 33 ]. DNAJC17 belongs to a class of cofactors called J-proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Since pharmacologic inhibition of HSP90 blocked the re-phosphorylation of SRSF10 and the recovery of splicing after heat shock, HSP90 is also likely necessary for this process [164]. Subsequent studies confirmed the role of HSP27 in splicing regulation and showed that a large number of genes are susceptible to HSP27 depletion [165].…”
Section: Rna Processing Regulation In Response To Heat Shockmentioning
confidence: 97%